Graphene Delivery Systems for Hierarchical Fiber Reinforced Composites. Issue 19 (5th February 2016) - Li, Yan; Zhang, Han; Peijs, Ton; Bilotti, Emiliano
ABSTRACT: Three different methods are evaluated for the introduction of graphene nanoplatelets (GNP) in hierarchical carbon- or glass fiber reinforced plastics. They involve; (1) direct infusion of GNP filled epoxy resin, (2) spray coating of GNP on fiber preforms and (3) the use of dissolvable thermoplastic interleaf carrier films. Direct infusion of GNP filled resin is the easiest method to deliver GNP into composite laminates but may lead to viscosity and filtration issues. Automated spray coating was set up to manufacture GNP modified carbon- or glass fiber fabrics, while graphene filled phenoxy interleaf films were manufactured by bar coating, both followed by resin infusion using neat epoxy resin to produce GNP modified epoxy laminates, without the disadvantages of GNP filled resins. No substantial difference in interlaminar shear strength (ILSS) for composites manufactured using the different delivery methods is found. However, the electrical conductivity of the GNP modified glass-fiber composites manufactured by spray coating of glass fabrics is two orders of magnitude higher than for laminates made by direct infusion of GNP modified resin.